SHIP LIGHTWEIGHT ESTIMATION AT CONCEPT DESIGN STAGE: CASE OF INDONESIA SINGLE ENDED RO-RO FERRIES - Dewanto, Christoforus Chandra; Nasirudin, Ahmad (Journal of Marine-Earth Science and Technology, 2022)
In recent years there have been many crossing vessels, especially those designed and built domestically. At the concept design stage, designers generally use the parent ship design method to determine the main dimension by taking one example of a reference ship with specifications close to the owner's requirements. However, this will be an obstacle if the existing ship specifications are unavailable, so designers must be able to perform initial calculations, especially predictions of the Lightweight (LWT). This paper introduces empirical formulas that utilize regression analysis to estimate LWT of Indonesia Single Ended Ro-Ro ferries. The formula of LWT based on Gross Tonnage (GT) requirements are presented.